The association between Chinese visceral adiposity index and hypertension among middle-aged and older population: a cross-sectional study based on CHARLS - Ma, Jialei; Ren, Jun; Chen, Yujia; Xue, Lili; Huang, Yufang; Qian, Jin; Chen, Yan; Lu, Mudan; Zhong, Yaqin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundIn recent years, obesity has become a serious public health issue. This study aims to investigate the association between the Chinese Visceral Adiposity Index (CVAI) and hypertension among the middle-aged and older population in China.MethodsData from the China Health and Retirement Longitudinal Study (CHARLS) 2015 wave were used. A 3-knot restricted cubic spline (RCS) was employed to analyze the dose-response relationship between CVAl and hypertension. Logistic regression model was used to explore the association between CVAI and hypertension, adjusting for confounding factors including age, sex, education level, smoking, alcohol consumption, body mass index (BMI), diabetes, hyperlipidemia, and heart disease.ResultsA total of 8,787 individuals were included in the study with a hypertension prevalence of 27.89%. A significant association between CVAI and hypertension was observed. Compared to those in the low CVAI category, hypertension was significantly associated with individuals in the high CVAI category in logistic regression (OR adjusted for confounding factors =1.967, 95% CI: 1.781, 2.172). The results showed that the risk of hypertension significantly increased with higher CVAI (trend test p < 0.001). Additionally, subgroup analyses demonstrated a stronger association between CVAI and hypertension among women (OR = 2.5, 95% CI: 2.18–2.88; P for interaction <0.001) and non-smokers (OR = 2.44, 95% CI: 2.14–2.78; P for interaction = 0.001).ConclusionCVAI may therefore potentially serve as a useful biomarker for identifying individuals at higher risk, and controlling visceral adiposity accumulation may be a potential target for the prevention and treatment of hypertension.